Battle of the sexes (1960) [videorecording (DVD)] - Sellers, Peter, 1925-1980; Morley, Robert; Cummings, Constance, 1910-2005 (KL Studio Classics, 2016)
Shaking the very foundation of a men-only company, an accomplished business woman attempts to contemporize a manufacturing company.